Budidaya Mint dan Pemanfaatannya untuk Minuman Kesehatan di SMP IT Khazanah Boarding School - Ermiyati; Nurdin; Yenita Morena; Muhammad Shalahuddin; Manyuk Fauzi; Andre Novan; Imam Suprayogi (Pelita Masyarakat, 2023)
Mint plants are generally grown on a small scale and are found growing wild in mountainous areas and in damp and watery places. This plant is able to adapt to tropical climates so that it can be cultivated. The purpose of this article is to provide counseling on how to cultivate mint leaves and use them as a fresh and healthy health drink at SMP IT Khazanah Boarding School. The method used is to provide counseling and practice it directly, how to cultivate and utilize mint plants as a fresh drink. Planting mint can be done by cutting existing plants. The trick is to cut the stalk about 1 cm above the branching. Then, remove some of the leaves on the stalks and submerge them in a container. Mint leaves have a distinctive spicy taste, fresh scent and have various benefits for the body, such as refreshing breathing, calming digestion, boosting immunity, and others. As for how to use it as a fresh drink for health which is combined with several ingredients such as Mint leaves, Lemons or Lime that have been cleaned, Honey or Sugar, and Hot Water. Then the lemons are cut into thin strips, then honey is added and the boiling hot water is poured into the container, then the mint leaves are dipped, and let stand for a moment so that the mint and lemon flavors are stronger then they can be served and drunk in warm conditions. The results obtained were that the teachers and students were very enthusiastic about participating in the community service activities carried out by the Riau University lecturer team from start to finish and almost all participants were excited to try planting, making drinks and enjoying fresh drinks from mint leaves.